(untitled) (Law Research Review Quarterly, 2025)
Patriarchal ideology on the impact of gender inequality occurs due to several factors, including: Customs, Lack of public understanding, high rates of early marriage in girls and economic limitations of the family. The purpose of this study is first to identify and analyze the causes of patriarchal ideology on the impact of gender inequality on mutual education in farming families. Second, to analyze the efforts that will be made to overcome patriarchal ideology on the impact of gender inequality on mutual education in farming families. The research method used in this study is a qualitative approach with a sociological juridical research type. The data sources used in this study are primary, secondary and tertiary data sources. The results of this study indicate that patriarchal ideology on the impact of gender inequality that occurs in society is still strong and has an impact on education, especially for girls. Therefore, efforts need to be made by the government and families to overcome gender discrimination in order to realize gender equality in women’s education in society. The theory in this study is (1) The theory of liberal feminism according to Mary Wallstonecraft is used to analyze gender discrimination that affects education and women’s rights. The reason for using this theory is because it focuses on women’s empowerment and the barriers that prevent women from gaining equal access to education with men. (2) Feminist legal theory according to Catharine Mackinon is used to analyze how legal efforts and government policies address gender inequality in education. The reason for using this theory is because this theory seeks to empower women by providing space for them to participate in the formation, implementation, and interpretation of law.